Establishment and application of a grading diagnostic model for early detection of severe fever with thrombocytopenia syndrome - Yao Hao; Yingchun Sun; Zhiyu Pan; Jing Sun; Manman Liang; Aiping Zhang; Jianghua Yang (Annals of Medicine)
Objective There is an urgent need to develop a reliable and efficient method for the early identification and diagnosis of severe fever with thrombocytopenia syndrome (SFTS).Methods This retrospective multicentre study analysed data from 363 patients with SFTS, which included general information and laboratory datas (white blood cell (WBC) count, platelet (PLT) count, aspartate aminotransferase (AST), creatine kinase (CK), creatine kinase-MB (CKMB), lactate dehydrogenase (LDH), hydroxybutyrate dehydrogenase (HBDH), amylase (AMY) and lipase (LIP), etc.). The indicators with higher positive rates were further combined and graded to establish the diagnostic method. The differential diagnosis was conducted with the same zoonotic diseases of fever and thrombocytopenia in the studied region. Finally, multicentre data were used to verify the method.Results The indicators with high positive rates were WBC, PLT, CK, CKMB, LDH and LIP. Analysis of combined indicators based on fever revealed that the combined positive rate of WBC and PLT was 79.34%, while that of WBC, PLT, AST, LDH, CK and LIP was 69.81%. This study analysed the combined positive rate of AST, LDH, CK and LIP, which was 75.47%. The reliability of this method was validated using multicentre data. For HFRS, the combined positive rate of WBC and PLT was 36.70% , and that of WBC, PLT, AST, LDH, CK and LIP was 27.33% . Additionally, the combined positive rate of AST, LDH, CK, LIP and serum creatinine (SCR) in HFRS was 48.50% (12.63% in SFTS). For scrub typhus, the combined positive rate of WBC and PLT was 12.00% , and that of WBC, PLT, AST, LDH, CK and LIP was 4.55% .Conclusions The present study integrated fever presentation, WBC count, PLT levels and biochemical markers to establish a method for early detection and grading diagnosis of SFTS. This study devised a direct and practical approach to diagnose and better understand the role of pathogens in the disease progression.